Sosialisasi Kawasan Keselamatan Operasi Penerbangan (KKOP) - Budi Prasetyo; Taufik Rohman; Solihin Solihin; Sundoro Sundoro; Nawang Kalbuana (Jurnal Pengabdian Kepada Masyarakat (JPKM) Langit Biru, 2021)
As one of the roles of universities, especially in the field of Aviation, The Indonesian Aviation Polytechnic is considered necessary to conduct socialization related to the Aviation Operations Safety Zone (KKOP) especially for the community around the airport area. This community service aims to provide knowledge, especially information about the world of aviation related to KKOP which is a land area and / or waters and air space around the airport used for aviation operations in order to ensure flight safety. This activity was carried out by socialization method to the community around Budiarto Airport and The Campus area of Politeknik Penerbangan Indonesia Curug by involving community leaders and youth in Kemuning Village, Legok District, Tangerang Regency, Banten Province for one day. The implementation of socialization also involves Cadets Diploma III Study Program Airport Operations who actively prepare materials accompanied by lecturers in the hope that Cadets can directly interact with the surrounding community in conveying the knowledge that has been learned on campus. With this KKOP Socialization activity, it is expected that the dissemination of knowledge related to KKOP in kemuning villagers is expected to increase the awareness of the community around Budiarto Airport and the Campus of The Indonesian Aviation Polytechnic Curug when conducting activities around the aviation operations area